Analysis of the Effectiveness of Online Learning Using E-learning Platforms in Indonesian Higher Education Institutions - David Darwin (Technologia Journal, 2025)
This study aims to analyze the effectiveness of online learning using E-learning platforms in Indonesian higher education institutions, particularly since the increased adoption of technology due to the COVID-19 pandemic. Online learning has become the primary solution for ensuring the continuity of education; however, its effectiveness remains in question. This research employs a quantitative approach by distributing questionnaires to 200 students from various universities across Indonesia. The findings indicate that E-learning offers flexibility and time efficiency, but still faces challenges such as limited internet access, lack of direct interaction, online learning fatigue, and uneven digital competence among both lecturers and students. Furthermore, the lack of diverse teaching methods and suboptimal infrastructure support also contribute to the low effectiveness of online learning. The study recommends the need to improve the quality of digital content, provide training for educators, and implement a more adaptive hybrid learning system. These findings are expected to serve as a reference for universities and policymakers in designing more effective and inclusive digital learning strategies in the future.